The Reality of Educational Quality Improvement in Tishreen University - A Field Study (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The research aimed to identify the reality of the application of methods to improve the quality of education  in Tishreen University, and to identify the degree of contribution of the quality assurance units in colleges under research in this improvement. The research has come to the set of results including: - decrease in using the methods of improving the quality of educational services at the colleges under research, - and lack in effective communication with the labor market to know his proposals to improve the quality of educational service, -and lack in attention to the proposals of students to improve the quality of educational service, -and decrease in contribution  of the  quality assurance units in surveyed colleges in this improvement, and in the development of  curriculum. واقع تحسين جودة التعليم في جامعة تشرين دراسة ميدانية هدف البحث إلى التعرف على واقع تطبيق أساليب تحسين جودة التعليم في جامعة تشرين، كما هدف إلى التعرف على درجة إسهام وحدات ضمان الجودة في الكليات محل البحث في هذا التحسين. وقد توصل البحث إلى مجموعة من النتائج أهمها: انخفاض استخدام أساليب تحسين جودة الخدمة التعليمية في الكليات محل البحث، وعدم التواصل الفعال مع سوق العمل للتعرف على اقتراحاته، وكذلك عدم الاهتمام باقتراحات الطلاب لتحسين هذه الجودة، وانخفاض درجة إسهام وحدات ضمان الجودة في الكليات المبحوثة في هذا التحسين، وفي تطوير المناهج الدراسية.